Improving Reading Comprehension through Contextual Guessing Technique at the Second Grade Students of SMA Negeri 1 Palopo - Sri Rahayu (Ethical Lingua: Journal of Language Teaching and Literature, 2015)
The objectives of this research were to find out the extent to which contextual guessing technique can improve the students’ reading comprehension and also to find out the students’ attitudes toward the use of contextual guessing technique in reading comprehension. The research used pre experimental design with one group pretest and posttest design. The research used purposive sampling technique where the sample consisted of 33 students who were taken in one class. The result of this research shows that there is siginificant difference between pre test and post test (5.03 < 8.90). The result of t-test value and t-table (17.31 > 2.037) also implies that there is a significant improvement in students’ reading comprehension after the treatment. It means that by using Contextual Guessing Technique is effecftive in improving students’ reading comprehension. Based on the classification table from the data of questionnaire, the writer found that the students’ attitudes toward the use of contextual guessing technique in reading comprehension is very positive. It is approved from 33 students whose their attitude have been researched, it is found that 18 (54.55%) students are classified as very positive, 14 (42.42%) students are classified as positive, 1 (3.03%) student is classified as doubt, and none of them are classified as negative and very negative.